(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
If we look at humanity’s historical development, our ancestors from ancient times considered water the source of their way of life. They realized that well-preserved irrigation facilities could be achieved only through the selfless work of many people.